Hypothalamic growth hormone receptor (GHR) controls hepatic glucose production in nutrient-sensing leptin receptor (LepRb) expressing neurons - Gillian Cady; Taylor Landeryou; Michael Garratt; John J. Kopchick; Nathan Qi; David Garcia-Galiano; Carol F. Elias; Martin G. Myers, Jr; Richard A. Miller; Darleen A. Sandoval; Marianna Sadagurski (Elsevier, 2017)
Objective: The GH/IGF-1 axis has important roles in growth and metabolism. GH and GH receptor (GHR) are active in the central nervous system (CNS) and are crucial in regulating several aspects of metabolism. In the hypothalamus, there is a high abundance of GH-responsive cells, but the role of GH signaling in hypothalamic neurons is unknown. Previous work has demonstrated that the Ghr gene is highly expressed in LepRb neurons. Given that leptin is a key regulator of energy balance by acting on leptin receptor (LepRb)-expressing neurons, we tested the hypothesis that LepRb neurons represent an important site for GHR signaling to control body homeostasis. Methods: To determine the importance of GHR signaling in LepRb neurons, we utilized Cre/loxP technology to ablate GHR expression in LepRb neurons (LeprEYFPΔGHR). The mice were generated by crossing the Leprcre on the cre-inducible ROSA26-EYFP mice to GHRL/L mice. Parameters of body composition and glucose homeostasis were evaluated. Results: Our results demonstrate that the sites with GHR and LepRb co-expression include ARH, DMH, and LHA neurons. Leptin action was not altered in LeprEYFPΔGHR mice; however, GH-induced pStat5-IR in LepRb neurons was significantly reduced in these mice. Serum IGF-1 and GH levels were unaltered, and we found no evidence that GHR signaling regulates food intake and body weight in LepRb neurons. In contrast, diminished GHR signaling in LepRb neurons impaired hepatic insulin sensitivity and peripheral lipid metabolism. This was paralleled with a failure to suppress expression of the gluconeogenic genes and impaired hepatic insulin signaling in LeprEYFPΔGHR mice. Conclusion: These findings suggest the existence of GHR-leptin neurocircuitry that plays an important role in the GHR-mediated regulation of glucose metabolism irrespective of feeding. Keywords: Growth hormone receptor, Hypothalamus, Leptin receptor, Glucose production, Liver